VARIABILITAS FENOTIPIK TANAMAN GAMBIR DI DESA TANJUNG, KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR - SEPRITA LIDAR; ENNY MUTRYARNY; TRISIA WULANTIKA (Universitas Lancang Kuning, 2018)
ABSTRACT Gambier is one commodity that is worth people's plantation economy and prospective for higher developed commercially in the future. Riau Province gambir Subdistrict where producers including the Gambier plantation had the most extensive is a subdistrict of Koto Kampar Kampar Regency acres 4,104 Upstream Research entitled